(untitled) (Филолошки студии, 2019)
We find mostly different forms of naming the Mrnjavchevy’s dynasty and its members throughout the Macedonian and the Serbian tradition and historiography. Accordingly, we analyze the problem concerning the King Volkashin’s name, the King Marko’s title and the name of Mrnjavchevy’s dynasty. Analyzing these forms, many factors should be taken into concideration. An interesting question appears if and how the different experiencing of the historical events could influence the transmission of their names throughout the traditions among the Macedonians and among the Serbians, or how the different emotions have determined both the traditional images and names in the folklore of the two peoples separately as well as their reflection in the historiography.